2009
DOI: 10.1093/annonc/mdn656
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib in patients with relapsed or refractory mantle cell lymphoma: updated time-to-event analyses of the multicenter phase 2 PINNACLE study

Abstract: Single-agent bortezomib is associated with lengthy responses and notable survival in patients with relapsed or refractory MCL, with considerable TTP and TTNT in responding patients, suggesting substantial clinical benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
188
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(195 citation statements)
references
References 31 publications
5
188
1
1
Order By: Relevance
“…A second investigated strategy to overcome Mcl-1 is to modify Mcl-1 complexes and its protein network. Bortezomib is among the most promising compounds in the treatment of MCL (25). Interestingly, the mixture of ABT-737 with bortezomib shows a synergistic effect, although no decrease of Mcl-1 protein expression is observed in the presence of bortezomib for up to 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second investigated strategy to overcome Mcl-1 is to modify Mcl-1 complexes and its protein network. Bortezomib is among the most promising compounds in the treatment of MCL (25). Interestingly, the mixture of ABT-737 with bortezomib shows a synergistic effect, although no decrease of Mcl-1 protein expression is observed in the presence of bortezomib for up to 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…ABT-737 synergizes with ara-C or bortezomib in ABT-737-resistant MCL cell lines ara-C and, more recently, bortezomib have been shown to be 2 important compounds in the treatment of MCL patients (24)(25)(26). ara-C exposure can induce a rapid decrease of Mcl-1 that occurs independently of caspase 3 (Fig.…”
Section: Combination Of Abt-737 and Flavopiridol Overcomes The Mcl-1-mentioning
confidence: 99%
“…44 The use of bortezomib, both as a single agent or in combination with a wide range of agents, is currently under investigation to improve survival in aggressive lymphomas. 6,9,14,47 Although bortezomib monotherapy is mainly ineffective in DLBCL cell lines, 29 the combination with immunochemotherapy has been shown to benefit a selected group of patients with relapsed or refractory ABC DLBCL 7 and in previously untreated patients with advance disease. 6 We have demonstrated that almost all of the DLBCL cell lines studied were primary resistant to bortezomib monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…6,8 -10 Bortezomib induces cell death by disrupting the endoplasmic reticulum (ER) stress responses in multiple myeloma 11,12 and in mantle cell lymphoma. [13][14][15] Moreover, preclinical studies demonstrate that bortezomib induces apoptosis and sensitizes tumor cells to chemotherapy and radiation. 16 The ER stress response is involved in aggressive phenotype and chemoresistance in many tumor types, including B-cell lymphomas.…”
mentioning
confidence: 99%
“…The first 'new drug' to be registered in relapsed MCL in the United States is bortezomib, since the first demonstrations of this selective and reversible proteasome 26S inhibitor's efficacy [22][23][24][25]. Even though the combination of bortezomib with rituximab and chemotherapy showed high response rates (up to 60-70%), the majority of these studies consists of small series of heavily pretreated patients and often comprises other histologies.…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%